Pengaruh Sistem Pembayaran terhadap Peningkatan Pendapatan UMKM di Banda Aceh - Zikri, Muhammad; Putra, Amansyah; Nabil Alghifari, Muhammad; Kurniawan, Sandi; Pahlevi, Reja (Sanger Journal: Social, Administration and Government Review, 2025)
This research aims to analyze the impact of cash and QRIS payment systems on the revenue growth of Micro, Small, and Medium-sized Enterprises (MSMEs) in Darussalam, Banda Aceh. Data were collected using a quantitative method through questionnaires distributed to business owners in coffee shops, kiosks, and photocopy businesses. The research findings indicate that in coffee shops, only cash payments had a significant influence on revenue (t-test = 0.046, p < 0.05), while QRIS payments had no effect (t-test = 0.562, p > 0.05). Similarly, in kiosks, cash payments had a significant impact on revenue (t-test = 0.025, p < 0.05), whereas QRIS payments did not (t-test = 0.562, p > 0.05). Conversely, in photocopy businesses, cash payments had no significant effect (t-test = 0.296, p > 0.05), but QRIS payments had a significant impact on revenue. These findings underscore the importance of understanding the characteristics of a business sector when choosing a payment system that can support MSME revenue growth.